DAMPAK COVID-19 TERHADAP PEMBIAYAAN BERMASALAH NASABAH DI BTN SYARIAH KCPS PANAKUKANG PADA TAHUN 2020 - Akram Ista; Rahman Ambo Masse; Muh. Irwan. T; Yuli Irawan Rasit (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
This study aims to determine the impact of Covid-19 on customer financing and to determine the impact of Covid-19 on banks, in this case BTN Syariah KCPS Pannakukang. This research is a qualitativeresearch conducted descriptively. The results of this study indicate that first, From the customer's perspective, namely the Covid-19 pandemic has greatly affected the customer's business merchandise sales, reduced and decreased income makes customers object to paying installments of financing, income during this pandemic is only to cover installment costs. the impact of this pandemic has made customers look for other income to meet their needs. Used to pay installments and basic daily needs. customers in terms of covering installments are half dead in looking for income to cover installment deposits.Second,From the perspective of the bank itself, namely BTN Syariah KCPS Panakukang, it has experienced a decrease in the level of community participation as an intermediary institution, the presence of Covid 19 has had an effect on turmoil in terms of views for leaders and employees regarding the best solution or solution that can be given to BTN KCPS Panakukang customers, the impact the Covid-19 pandemic for BTN Syariah KCPS Panakukang itself, namely issuing a special policy for BTN Syariah KCPS Panakukang customers.